Metabolomic and metagenomic analyses of the Chinese mitten crab Eriocheir sinensis after challenge with Metschnikowia bicuspidata - Jiang, Hongbo; Bao, Jie; Xing, Yuenan; Cao, Gangnan; Li, Xiaodong; Chen, Qijun (Frontiers in Microbiology, 2022)
Milky disease caused by Metschnikowia bicuspidata fungus has significantly harmed the Chinese mitten crab Eriocheir sinensis aquaculture industry. However, the effect of M. bicuspidata infection on the metabolism and intestinal flora of the crab remains unclear. In this study, we aimed to explore the changes in the metabolism and intestinal flora E. sinensis after 48 h of infection with M. bicuspidata, using metabolomic and metagenomic analyses. Metabolomic analysis results revealed 420 significantly different metabolites between the infected and control groups, and these metabolites were enriched in 58 metabolic pathways. M. bicuspidata infection decreased the levels of metabolites related to amino acid biosynthesis, the tricarboxylic acid cycle, as well as lysine, histidine, linolenic, arachidonic, and linoleic acid metabolism. These results indicated that M. bicuspidata infection significantly affected the energy metabolism, growth, and immunity of E. sinensis. The results of metagenomic analysis showed that the anaerobes and ascomycetes populations significantly increased and decreased, respectively, after M. bicuspidata infection. These changes in intestinal flora significantly upregulated metabolic and synthetic pathways while downregulating immunity-related pathways. The results of integrated metabolomic and metagenomic analyses showed that 55 differentially expressed genes and 28 operational taxonomic units were correlated with 420 differential metabolites. Thus, the intestinal flora changes caused by M. bicuspidata infection also affected the metabolites. This study provides novel insights into the metabolic-and intestinal microflora-based effects of M. bicuspidata infection in E. sinensis, as well as a theoretical basis for the interaction between fungi and crustaceans.